HUBUNGAN EXSPLOSIVE POWER OTOT LENGAN DENGAN HASIL LONG SERVE DALAM PERMAINAN BULUTANGKIS PADA EXSTRAKURIKULER SISWA SMA NEGERI 2 SIAK KECIL KABUPATEN BENGKALIS - Saputra, Alis; ', Saripin; August, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The results of the author's observation on Student SMAN 2 Siak Kecil Bengkalis in extracurricular badminton, students have not been too optimal in long serve, it can be seen students often fail to do a long serve well during training, learning in school, a match between the class and other matches. it is a challenge that needs to be considered of any good society, parents, teachers, and coaches. so that students excel in the game of badminton. the purpose of this research is to know or see if there is a relationship exsplosive arm muscle power to serve long results in a game of badminton on Ekstrakurikuler Students SMAN 2 Siak Kecil Bengkalis. As for the sample are students of extracurricular of 12 students, while the instrument of this study is to collect data to measure muscle power exsplosive sleeves and long punches tests serve.data obtained in the analysis by using normality test, test and test Liliefors kolersi.test analysis can be in view kolersi 0.60 to 0.799 is 0:55. then the hypothesis is accepted, in other words: there is a significant relationship exsplosive arm muscle power to serve long results in a game of badminton in extracurricular student SMAN 2 Siak Kecil Bengkalis.Keywords: Exsplosive Muscle Power And Long Sleeves Serve